The Innovative Bureaucracy Bureaucracy in an age of fluidity - Alexander Styhre (by Routledge, 2007)
It probably matters that I was born, raised and have spent most of my life in a modern Western social-democratic country praising egalitarian values, and, most importantly, spending a considerable amount of resources on the public sector – but I have never been fully able to understand all the ready-made complaints and critiques about bureaucracy in popular culture and the social theory and organization theory literature that I have engaged with over the last ten years. For me, bureaucracy is not part of the problem but part of the solution to a range of social concerns and objectives. Without doubt, my own personal experiences from reasonably well-functioning bureaucratic organizations catering a range of services in Swedish municipalities and the state administration are not fully compatible with other’s experiences of bureaucracy. I have, over the years, heard numerous complaints, anecdotes and more or less amusing stories from my friends and colleagues about encounters with Belgian immigration officers, Italian university administrators, the Chinese railways, the Philippinian police corps and a variety of other representatives of bureaucratic organizations that have been deemed by my interlocutors to function less smoothly and transparently than one may hope for. Furthermore, newspapers continuously report about the presence of corruption, bribery, nepotism and oligarchies in most parts of the world. Such news is discouraging for anyone having faith in public administration, so I am fully aware that I may have been lucky to be able to testify to my belief in bureaucracy.